Content analysis of nutritional information in paediatric oral health education leaflets - Amit Arora; Jenny Doan; Jessamine Martinez; Colin Phan; Gregory S. Kolt; Sameer Bhole; Mark Fort Harris; Jane Anne Scott; Debra Hector (BMC, 2017)
Abstract Background The aim of this study was to determine if paediatric oral health education leaflets with a food and nutritional focus provide messages that are clear and consistent with the current Australian Dietary Guidelines and the Infant Feeding Guidelines. Methods Forty-three leaflets aimed at parents were sourced from Australian state and territory Health Departments, oral health industry partners and commercial organisations, and a content analysis was performed. Recommendations on food and drink type, consumption frequency and general diet and nutrition advice were considered and cross-referenced with the Australian Dietary Guidelines and the Infant Feeding Guidelines to identify areas of consistency and discrepancy. Results Twenty leaflets recommended reducing the consumption of sugary and/or acidic food, while 23 leaflets recommended reducing the consumption of sugary and/or acidic drinks. The majority of the leaflets advised water (n = 35) and milk (n = 23) to drink. Although 33 leaflets encouraged a healthy diet, seven of these did not specify what a healthy diet was. Twenty-eight leaflets provided early childhood-related (0-2 years) feeding advice. Confusing messages were found in nine leaflets, with ambiguous recommendations that were open to individual interpretation. Conclusions There were some inconsistencies between the leaflets and the dietary and infant feeding guidelines in Australia; and across the leaflets, as not all important messages were included in any one leaflet. Government Health Departments and other relevant agencies should ensure that advisory messages regarding diet, particularly those with dental implications, are clear, complete and consistent across all dental educational leaflets.